A hora da palavra: intertextualidade em Caetano Veloso - Barbosa, Jorge Luís Verly (2006)
The lyrics of Caetano Veloso are connected to the best poetical tradition, verses by nature, form and significance. They are setting by an inexhaustible self-reflection, endorsed by the world and the culture. Dialogical too in concern with the many literary and poetical traditions. Analyzing them by this way, this academic essay was constructed from a research about the connections between this poetic and the tradition, trough the studies of intertextuality. On this view, will show the authorial marks, direct and indirect, of tradition in the poetic production of Caetano Veloso, through of parodies, paraphrases, pastiches, quotations, references, allusions and others intertextual acts showed by the analysis of some of his poems.